Negative electrode
Patent Information
- Application Number
- JP2022038807
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-14
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-03-14
AI Technical Summary
【0016】 本開示は、電池の抵抗低減が可能な負極を提供することができる。
Smart Images

Figure 0007652110000002 
Figure 0007652110000003 
Figure 0007652110000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode. [Background technology]
[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. In the automobile industry, too, development of high-output, high-capacity batteries for electric vehicles or hybrid vehicles is underway.
[0003] Patent Document 1 discloses a secondary battery that can fully exhibit excellent output performance when a magnetic field is applied and graphite is arranged vertically by specifying the porosity of the positive electrode composite and the negative electrode composite, and the aspect ratio, perpendicularity, and composite density of the negative electrode active material.
[0004] Patent Document 2 discloses a method for producing a negative electrode for a battery, which is characterized by forming a hardened layer of a graphite-based negative electrode active material composition on a negative electrode current collector under a magnetic field.
[0005] Patent Document 3 discloses graphite powder characterized in that natural graphite particles are processed into spherical shapes by impact and / or grinding. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-089574 A [Patent Document 2] JP 1998-321219 A [Patent Document 3] JP 2006-083030 A Summary of the Invention [Problem to be solved by the invention]
[0007] Further reduction in battery resistance is required.
[0008] The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide a negative electrode capable of reducing the resistance of a battery. [Means for solving the problem]
[0009] The negative electrode of the present disclosure is a negative electrode for a lithium ion secondary battery, The negative electrode includes a negative electrode current collector and a negative electrode layer, The negative electrode layer includes a negative electrode active material and a binder, The elastic modulus of the binder is greater than 811 MPa; When the X-ray diffraction intensity of the (110) plane of the negative electrode active material is I(110) and the X-ray diffraction intensity of the (004) plane is I(004), The negative electrode active material is characterized in that its degree of orientation I(110) / I(004), obtained by dividing I(110) by I(004), is greater than 0.23.
[0010] In the negative electrode of the present disclosure, the aspect ratio of the negative electrode active material may be greater than 1.2.
[0011] In the negative electrode of the present disclosure, the negative electrode active material may be flake graphite.
[0012] In the negative electrode of the present disclosure, the binder may have an elastic modulus of 3000 MPa or less.
[0013] In the negative electrode of the present disclosure, the binder may have an elastic modulus of 1886 MPa or less.
[0014] In the negative electrode of the present disclosure, the binder may have an elastic modulus of 1027 MPa or more.
[0015] In the negative electrode of the present disclosure, the degree of orientation I(110) / I(004) may be 0.25 or more. Effect of the Invention
[0016] The present disclosure can provide a negative electrode capable of reducing the resistance of a battery. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a graph showing an example of the relationship between strain and test force. [Diagram 2] FIG. 2 is a diagram showing an example of the relationship between the current and the voltage difference ΔV. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments of the present disclosure will be described. In addition, matters other than those specifically mentioned in this specification and necessary for the implementation of the present disclosure (for example, the general configuration and manufacturing process of the negative electrode that do not characterize the present disclosure) can be understood as design matters of a person skilled in the art based on the conventional technology in the field. The present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit. Furthermore, any combination of upper and lower limits in a numerical range can be used.
[0019] The negative electrode of the present disclosure is a negative electrode for a lithium ion secondary battery, The negative electrode includes a negative electrode current collector and a negative electrode layer, The negative electrode layer includes a negative electrode active material and a binder, The elastic modulus of the binder is greater than 811 MPa; When the X-ray diffraction intensity of the (110) plane of the negative electrode active material is I(110) and the X-ray diffraction intensity of the (004) plane is I(004), The negative electrode active material is characterized in that its degree of orientation I(110) / I(004), obtained by dividing I(110) by I(004), is greater than 0.23.
[0020] Depending on the type of binder used in the negative electrode layer, it may not be possible to fully exert its effect as a binder. This is because the perpendicularity of the negative electrode active material when the negative electrode layer is pressed varies depending on the softness of the binder used in the negative electrode layer. In the negative electrode of the present disclosure, a binder with a high elastic modulus (hard binder) is used. According to the negative electrode of the present disclosure, when a magnetic field is applied to press the negative electrode layer in which the negative electrode active material is arranged in a vertical direction, the hardness of the binder suppresses deformation of the binder, making it possible to reduce collapse of the negative electrode active material from the vertical direction and maintain the orientation of the negative electrode active material, thereby reducing the resistance of the battery and improving the input / output performance of the battery. Although the collapse of the negative electrode active material can be suppressed by increasing the amount of a soft binder, the increase in the amount of the binder increases the resistance of the battery. On the other hand, the negative electrode of the present disclosure allows the amount of the binder to be reduced compared to the case of using a soft binder. According to the negative electrode of the present disclosure, by combining a negative electrode active material with a high degree of orientation with a binder with a high elastic modulus, the resistance of the battery can be reduced and the input / output performance of the battery can be improved.
[0021] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode layer.
[0022] [Negative electrode layer] The negative electrode layer contains at least a negative electrode active material and a binder, and optionally contains a solid electrolyte, a conductive material, a thickener, and the like.
[0023] Examples of the negative electrode active material include graphite, mesocarbon microbeads (MCMB), highly oriented pyrolytic graphite (HOPG), hard carbon, and soft carbon. The graphite may be spheroidized graphite, flake graphite (hereinafter sometimes referred to as flake graphite), etc., and among these, flake graphite is preferred from the viewpoint of reducing resistance. The shape of the negative electrode active material is not particularly limited, and may be particulate, flake, plate, or the like.
[0024] The aspect ratio of the negative electrode active material may be greater than 1.2, and may be 2.0 or greater. The aspect ratio of the negative electrode active material may be 10 or less. The aspect ratio is expressed as a / b, where a is the length in the long axis direction of the negative electrode active material and b is the length in the short axis direction. For example, the aspect ratio of graphite is determined by determining the length A in the long axis direction and the length B in the short axis direction of graphite by observation using a TEM (transmission electron microscope) or a SEM (scanning electron microscope). In addition, when the graphite has a thickness direction such as a scale shape, the thickness is defined as the length B in the short axis direction. As the aspect ratio of the negative electrode active material (e.g., graphite) increases, the anisotropy of the electronic resistance of the negative electrode active material itself (i.e., the resistance varies depending on the orientation direction) tends to increase, so that the resistance can be reduced by applying a magnetic field to the negative electrode active material (e.g., a negative electrode active material with an aspect ratio greater than 1.2) as described later to orient it (typically oriented in a direction approximately perpendicular to the negative electrode current collector).
[0025] The binder may be any one having a modulus of elasticity of more than 811 MPa, and one or a combination of two or more of the materials conventionally used as binders may be used. Examples of binders include acrylic acid binders, polyimide binders, polyamide binders, cellulose polymers such as carboxymethyl cellulose (CMC), methyl cellulose (MC), cellulose acetate phthalate (CAP), and hydroxypropyl methyl cellulose (HPMC), fluorine resins such as polyvinyl alcohol (PVA) and polytetrafluoroethylene (PTFE), vinyl acetate copolymers, and rubbers such as styrene butadiene rubber (SBR), etc. The materials exemplified above can be used for the purpose of exerting a function as a thickener in addition to the function as a binder. The elastic modulus of the binder may be 1027 MPa or more, 3000 MPa or less, or 1886 MPa or less.
[0026] The conductive material used in the negative electrode layer may be the same as that exemplified in the positive electrode layer. The solid electrolyte used in the negative electrode layer may be the same as that exemplified in the solid electrolyte layer.
[0027] The thickness of the negative electrode layer is not particularly limited, but may be, for example, 10 to 100 μm.
[0028] The content of the negative electrode active material in the negative electrode layer is not particularly limited, and may be, for example, 20% by mass to 99% by mass.
[0029] When the X-ray diffraction intensity of the (110) plane of the negative electrode active material is defined as I(110) and the X-ray diffraction intensity of the (004) plane is defined as I(004), The degree of orientation of the negative electrode active material, I(110) / I(004), obtained by dividing I(110) by I(004), may be greater than 0.23, may be 0.25 or more, or may be 0.29 or more. The upper limit of the degree of orientation is not particularly limited, but may be, for example, 0.80 or less.
[0030] The negative electrode layer is formed, for example, as follows. First, a paste-like (paste-like includes slurry and ink-like) negative electrode mixture containing the negative electrode active material (for example, flake graphite), binder (for example, SBR), thickener (for example, CMC), etc., and further containing a solvent (for example, water) as necessary, is prepared (prepared, purchased, etc.), and the negative electrode mixture is applied (applied) to the surface of the negative electrode current collector. The method of applying the negative electrode mixture to the negative electrode current collector is not particularly limited, and examples thereof include a doctor blade method, a metal mask printing method, an electrostatic application method, a dip coating method, a spray coating method, a roll coating method, a gravure coating method, and a screen printing method.
[0031] Next, in order to increase the degree of orientation of the negative electrode active material to more than 0.23, a magnetic field may be applied to the negative electrode mixture applied to the surface of the negative electrode current collector (which may be a negative electrode mixture in a state where the solvent remains and is not yet dried). A magnetic field generator such as a permanent magnet or an electromagnetic coil is used to apply a magnetic field such that the direction of the magnetic field lines is perpendicular to the surface of the negative electrode current collector. The strength of the magnetic field applied to the negative electrode mixture applied to the surface of the negative electrode current collector may be, for example, 0.08 T to 1 T, or may be 0.3 to 0.6 T. The time for which the magnetic field is applied to the negative electrode mixture may be, for example, 1 second to 180 seconds. The negative electrode active material in the negative electrode mixture applied to the negative electrode current collector tends to be oriented so that the (004) plane of the negative electrode active material and the surface (wide surface) of the negative electrode current collector are approximately parallel (for example, oriented so that the angle θn between the (004) plane of the negative electrode active material and the surface of the negative electrode current collector is 0°≦θn≦30°). By applying a magnetic field to the negative electrode mixture as described above, the (004) plane of the negative electrode active material in the negative electrode mixture can be oriented so as to rise up against the negative electrode current collector (for example, oriented so that the angle θn between the (004) plane of the negative electrode active material and the surface of the negative electrode current collector is 60°≦θn≦90°). When the negative electrode active material is graphite, the "(004) plane of the negative electrode active material" refers to a layer plane of the graphite in a layered structure (a plane parallel to the graphite layer), and a plane parallel to the carbon network of the graphene sheet constituting the graphite.
[0032] Next, after applying the magnetic field, the negative electrode mixture applied to the negative electrode current collector is dried to form a negative electrode layer. For example, the negative electrode mixture applied to the negative electrode current collector can be dried by passing the negative electrode mixture to which the magnetic field has been applied through a drying furnace. The drying temperature at this time may be, for example, 80° C. to 180° C. The drying time may be, for example, 10 seconds to 120 seconds. After the negative electrode layer is formed, the obtained negative electrode may be rolled (pressed) as necessary. As the rolling method, a conventionally known rolling method such as a flat plate press and a roll press can be adopted. The pressing pressure may be, for example, a linear pressure of 1 kN / m or more and 4 kN / m or less. If the pressing pressure is within the above range, the negative electrode active material oriented to stand up against the negative electrode current collector by applying a magnetic field to the negative electrode mixture when forming the negative electrode layer maintains the oriented state. On the other hand, if the pressing pressure is too large, the influence of rolling is large, so that the negative electrode active material oriented by applying a magnetic field lies down (becomes approximately parallel) against the negative electrode current collector, which may reduce the diffusibility of lithium ions and increase the resistance. In the manner described above, a negative electrode is produced, which includes a negative electrode current collector and a negative electrode layer formed on the surface of the negative electrode current collector.
[0033] [Negative electrode current collector] The material of the negative electrode current collector may be a material that does not alloy with Li, and examples of such materials include SUS, copper, and nickel. Examples of the shape of the negative electrode current collector include foil and plate. The planar shape of the negative electrode current collector is not particularly limited, and examples of such shapes include a circle, an ellipse, a rectangle, and any polygon. The thickness of the negative electrode current collector varies depending on the shape, and may be, for example, within a range of 1 μm to 50 μm, or within a range of 5 μm to 20 μm.
[0034] [battery] The negative electrode of the present disclosure is for a lithium ion secondary battery. The lithium ion secondary battery of the present disclosure may include a positive electrode, an electrolyte layer, and a negative electrode. The lithium ion secondary battery may be an aqueous lithium ion secondary battery, a non-aqueous lithium ion secondary battery, an all-solid-state lithium ion secondary battery, or the like. Examples of the shape of the lithium ion secondary battery include a coin type, a laminate type, a cylindrical type, and a square type. The use of the lithium ion secondary battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, the battery may be used as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. The battery in the present disclosure may also be used as a power source for moving objects other than vehicles (e.g., railways, ships, and aircraft), and may also be used as a power source for electrical appliances such as information processing devices.
[0035] [Positive electrode] The positive electrode has a positive electrode layer, and optionally a positive electrode current collector.
[0036] [Positive electrode layer] The positive electrode layer contains a positive electrode active material, and may contain, as optional components, a conductive material, a solid electrolyte, a binder, and the like.
[0037] There is no particular limitation on the type of positive electrode active material, and any material that can be used as an active material for an all-solid-state battery can be used. Examples of the positive electrode active material include lithium alloys, LiCoO2, and LiNi x M 1-x O2 (wherein x satisfies 0.5≦x<1, and M is at least one element selected from the group consisting of Co, Mn, and Al), LiMnO2, Li-Mn spinel substituted with a different element, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, Li4SiO4, transition metal oxides, TiS2, Si, SiO2, Si alloys, and lithium-storing intermetallic compounds. The Li-Mn spinel substituted with different elements is, for example, LiMn 1.5 Ni 0.5 O4, LiMn 1.5 Al 0.5 O4, LiMn 1.5 Mg 0.5 O4, LiMn 1.5 Co 0.5 O4, LiMn 1.5 Fe 0.5 O4 and LiMn 1.5 Zinc 0.5 It is O4 grade. Lithium titanate is, for example, Li4Ti5O 12 etc. Examples of lithium metal phosphates include LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Examples of transition metal oxides include V2O5, MoO3, etc. Examples of lithium storage intermetallic compounds include Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb, etc. Lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Examples include Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At. Examples of the Si alloy include alloys with metals such as Li, and may also be alloys with at least one metal selected from the group consisting of Sn, Ge, and Al. The shape of the positive electrode active material is not particularly limited, and may be particulate. When the positive electrode active material is particulate, the positive electrode active material may be primary particles or secondary particles. A coating layer containing a Li-ion conductive oxide may be formed on the surface of the positive electrode active material, because this can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of Li-ion conductive oxides include LiNbO3 and Li4Ti5O 12 , and Li3PO4. The thickness of the coating layer is, for example, 0.1 nm or more, and may be 1 nm or more. On the other hand, the thickness of the coating layer is, for example, 100 nm or less, and may be 20 nm or less. The coating layer may cover, for example, 70% or more, or 90% or more of the surface of the positive electrode active material.
[0038] The conductive material may be a known material, such as a carbon material and metal particles. The carbon material may be at least one selected from the group consisting of acetylene black, furnace black, VGCF, carbon nanotubes, and carbon nanofibers. In particular, from the viewpoint of electronic conductivity, at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers may be used. The metal particles may be particles of Ni, Cu, Fe, SUS, etc. The content of the conductive material in the positive electrode layer is not particularly limited.
[0039] As the solid electrolyte, the same ones as those exemplified in the solid electrolyte layer can be exemplified. The content of the solid electrolyte in the positive electrode layer is not particularly limited, but may be, for example, within a range of 1 mass % to 80 mass % when the total mass of the positive electrode layer is taken as 100 mass %.
[0040] Examples of the binding agent (binder) include polyacrylonitrile, polyacrylic acid, polymethyl ester of acrylic acid, polyethyl ester of acrylic acid, polyhexyl ester of acrylic acid, polymethacrylic acid, polymethyl ester of methacrylic acid, polyethyl ester of methacrylic acid, polyhexyl ester of methacrylic acid, acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), and styrene butadiene rubber (SBR). The content of the binder in the positive electrode layer is not particularly limited.
[0041] The thickness of the positive electrode layer is not particularly limited, but may be, for example, 10 to 100 μm.
[0042] The positive electrode layer can be formed by a conventionally known method. For example, a positive electrode active material and, if necessary, other components are put into a solvent and stirred to prepare a paste for forming a positive electrode layer, and the paste for forming a positive electrode layer is applied onto one side of a support and dried to obtain a positive electrode layer. Examples of the solvent include butyl acetate, butyl butyrate, mesitylene, tetralin, heptane, and N-methyl-2-pyrrolidone (NMP). The method for applying the paste for forming a positive electrode layer onto one surface of the support is not particularly limited, and examples thereof include the same methods as those exemplified as the method for applying the negative electrode mixture to the negative electrode current collector. The support can be appropriately selected from those having self-supporting properties and is not particularly limited. For example, metal foils such as Cu and Al can be used.
[0043] As another method for forming the positive electrode layer, the positive electrode layer may be formed by pressure molding a powder of a positive electrode mixture containing a positive electrode active material and other components as necessary. When the powder of the positive electrode mixture is pressure molded, a surface pressure of 1 MPa to 2000 MPa and a linear pressure of 1 ton / cm to 100 ton / cm are usually applied. The method of applying pressure is not particularly limited, but examples thereof include a method of applying pressure using a plate press, a roll press, or the like.
[0044] [Positive electrode current collector] The positive electrode current collector may be a known metal that can be used as a current collector for a battery. Examples of such metals include metal materials containing one or more elements selected from the group consisting of Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge, and In. Examples of the positive electrode current collector include SUS, aluminum, nickel, iron, titanium, and carbon. The shape of the positive electrode current collector is not particularly limited, and may be in various shapes such as a foil shape, a mesh shape, etc. The thickness of the positive electrode current collector varies depending on the shape, but may be, for example, in the range of 1 μm to 50 μm, or in the range of 5 μm to 20 μm.
[0045] [Electrolyte layer] The electrolyte layer includes at least an electrolyte. The electrolyte may be an aqueous electrolyte solution, a non-aqueous electrolyte solution, a gel electrolyte, a solid electrolyte, etc. These may be used alone or in combination of two or more.
[0046] The solvent of the aqueous electrolyte solution contains water as a main component. That is, based on the total amount of the solvent (liquid component) constituting the electrolyte solution (100 mol%), water may account for 50 mol% or more, particularly 70 mol% or more, and further 90 mol% or more. On the other hand, there is no particular upper limit to the proportion of water in the solvent.
[0047] The solvent contains water as a main component, but may contain a solvent other than water. Examples of the solvent other than water include one or more selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds, and hydrocarbons. The solvent other than water may be 50 mol% or less, particularly 30 mol% or less, and further 10 mol% or less, based on the total amount of the solvent (liquid component) constituting the electrolytic solution (100 mol%).
[0048] The aqueous electrolyte used in the present disclosure includes an electrolyte. The electrolyte for the aqueous electrolyte may be a conventionally known one. Examples of the electrolyte include lithium salts, nitrates, acetates, and sulfates of imide acid compounds. Specific examples of the electrolyte include lithium bis(fluorosulfonyl)imide (LiFSI; CAS No. 171611-11-3), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI; CAS No. 90076-65-6), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI; CAS No. 132843-44-8), lithium bis(nonafluorobutanesulfonyl)imide (CAS No. 119229-99-1), lithium nonafluoro-N-[(trifluoromethane)sulfonyl]butanesulfonylamide (CAS No. 176719-70-3), lithium N,N-hexafluoro-1,3-disulfonylimide (CAS No. 189217-62-7), CH3COOLi, LiPF6, LiBF4, Li2SO4, and LiNO3.
[0049] The concentration of the electrolyte in the aqueous electrolyte solution can be appropriately set according to the desired battery characteristics, within a range not exceeding the saturation concentration of the electrolyte in the solvent, because if a solid electrolyte remains in the aqueous electrolyte solution, the solid may inhibit the battery reaction. For example, when LiTFSI is used as the electrolyte, the aqueous electrolyte may contain 1 mol or more of LiTFSI per kg of water, particularly 5 mol or more, and further 7.5 mol or more. The upper limit is not particularly limited, and may be, for example, 25 mol or less.
[0050] The non-aqueous electrolyte solution used generally contains a lithium salt and a non-aqueous solvent. Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2(Li-TFSI), LiN(SO2C2F5)2, and LiC(SO2CF3)3. Examples of the non-aqueous solvent include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, sulfolane, acetonitrile (AcN), dimethoxymethane, 1,2-dimethoxyethane (DME), 1,3-dimethoxypropane, diethyl ether, tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide (DMSO), and mixtures thereof. From the viewpoint of ensuring a high dielectric constant and a low viscosity, the solvent may be a mixture of a cyclic carbonate compound having a high dielectric constant and a high viscosity, such as EC, PC, or BC, and a chain carbonate compound having a low dielectric constant and a low viscosity, such as DMC, DEC, or EMC, or a mixture of EC and DEC. The concentration of the lithium salt in the non-aqueous electrolyte may be, for example, 0.3 to 5M.
[0051] A gel electrolyte is generally a gel formed by adding a polymer to a non-aqueous electrolyte solution. Specifically, the gel electrolyte can be obtained by adding a polymer such as polyethylene oxide, polypropylene oxide, polyacrylonitrile, polyvinylidene fluoride (PVdF), polyurethane, polyacrylate, or cellulose to the nonaqueous electrolyte solution described above and gelling the solution.
[0052] The electrolyte layer may be impregnated with an electrolyte such as the above-mentioned aqueous electrolyte solution, and a separator may be used to prevent contact between the positive electrode layer and the negative electrode layer. The material of the separator is not particularly limited as long as it is a porous film, and examples thereof include resins such as polyethylene (PE), polypropylene (PP), polyester, cellulose, and polyamide, among which polyethylene and polypropylene are also suitable. The separator may have a single layer structure or a multi-layer structure. Examples of the multi-layer structure separator include a separator with a two-layer structure of PE / PP, or a separator with a three-layer structure of PP / PE / PP or PE / PP / PE. The separator may be a nonwoven fabric such as a resin nonwoven fabric or a glass fiber nonwoven fabric.
[0053] [Solid electrolyte layer] The electrolyte layer may be a solid electrolyte layer made of a solid. The solid electrolyte layer includes at least a solid electrolyte. As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in an all-solid-state battery can be appropriately used, and examples of such solid electrolytes include inorganic solid electrolytes such as sulfide-based solid electrolytes, oxide-based solid electrolytes, hydride-based solid electrolytes, halide-based solid electrolytes, and nitride-based solid electrolytes. The sulfide-based solid electrolyte may contain sulfur (S) as a main component of the anion element. The oxide-based solid electrolyte may contain oxygen (O) as a main component of the anion element. The hydride-based solid electrolyte may contain hydrogen (H) as a main component of the anion element. The halide-based solid electrolyte may contain halogen (X) as a main component of the anion element. The nitride-based solid electrolyte may contain nitrogen (N) as a main component of the anion element.
[0054] The sulfide-based solid electrolyte may be a sulfide glass, a crystallized sulfide glass (glass ceramics), or a crystalline material obtained by subjecting a raw material composition to a solid-phase reaction treatment. The crystalline state of the sulfide-based solid electrolyte can be confirmed, for example, by subjecting the sulfide-based solid electrolyte to powder X-ray diffraction measurement using CuKα radiation.
[0055] The sulfide glass can be obtained by subjecting a raw material composition (e.g., a mixture of Li2S and P2S5) to an amorphous process, such as mechanical milling.
[0056] Glass ceramics can be obtained, for example, by heat treating a sulfide glass. The heat treatment temperature may be any temperature higher than the crystallization temperature (Tc) of the sulfide glass observed by thermal analysis, and is usually 195° C. or higher. On the other hand, there is no particular upper limit to the heat treatment temperature. The crystallization temperature (Tc) of the sulfide glass can be measured by differential thermal analysis (DTA). The heat treatment time is not particularly limited as long as the desired crystallinity of the glass ceramic is obtained, but is, for example, within the range of 1 minute to 24 hours, and particularly within the range of 1 minute to 10 hours. The method of heat treatment is not particularly limited, but may be, for example, a method using a baking furnace.
[0057] Examples of oxide-based solid electrolytes include solid electrolytes containing Li, Y (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Specific examples of oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x )O 12 (0≦x≦2), Li5La3Nb2O 12 perovskite-type solid electrolytes such as (Li,La)TiO3, (Li,La)NbO3, (Li,Sr)(Ta,Zr)O3; Nasicon-type solid electrolytes such as Li(Al,Ti)(PO4)3 and Li(Al,Ga)(PO4)3; Li-PO-based solid electrolytes such as Li3PO4 and LIPON (a compound in which some of the O in Li3PO4 is replaced with N); and Li-BO-based solid electrolytes such as Li3BO3 and a compound in which some of the O in Li3BO3 is replaced with C. In the present disclosure, the notation "(A,B,C)" in a chemical formula means "at least one selected from the group consisting of A, B, and C."
[0058] The hydride-based solid electrolyte has, for example, Li and a complex anion containing hydrogen. The complex anion is, for example, (BH4) - , (NH2) - , (AlH4) - , and (AlH6) 3- etc.
[0059] The halide-based solid electrolyte is, for example, represented by the following composition formula (1). Li α M β X γ ...Equation (1) In the composition formula (1), α, β, and γ are each independently a value greater than 0. M includes at least one element selected from the group consisting of metal elements and metalloid elements other than Li. X includes at least one element selected from the group consisting of F, Cl, Br, and I. In the present disclosure, the "metalloid elements" are B, Si, Ge, As, Sb, and Te. The "metal elements" are all elements in Groups 1 to 12 of the periodic table except for hydrogen, and all elements in Groups 13 to 16 of the periodic table except for B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. In other words, the "metalloid elements" or "metal elements" are a group of elements that can become cations when forming an inorganic compound with a halogen element. More specifically, examples of halide-based solid electrolytes include Li3YX6, Li2MgX4, Li2FeX4, LiAlX4, LiGaX4, LiInX4, Li3AlX6, Li3GaX6, and Li3InX6, where X is at least one selected from the group consisting of F, Cl, Br, and I.
[0060] An example of the nitride-based solid electrolyte is Li3N.
[0061] The solid electrolyte may be in the form of particles from the viewpoint of ease of handling. The average particle size of the solid electrolyte particles is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more, while the average particle size of the solid electrolyte particles is, for example, 25 μm or less, and may be 10 μm or less.
[0062] In this disclosure, the average particle size of particles is the volume-based median diameter (D50) value measured by laser diffraction / scattering particle size distribution measurement, unless otherwise specified. In this disclosure, the median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles is half (50%) of the total volume when the particles are arranged in order from the smallest particle size.
[0063] The solid electrolyte may be used alone or in combination of two or more kinds. When two or more kinds of solid electrolytes are used, the two or more kinds of solid electrolytes may be mixed, or two or more layers of the solid electrolyte may be formed to form a multilayer structure. The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more, and may be in the range of 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or may be 100% by mass.
[0064] The solid electrolyte layer may contain a binder from the viewpoint of expressing plasticity, etc. Examples of such binders include the materials exemplified as the binders used in the positive electrode layer. However, in order to facilitate high output, the binder may be contained in the solid electrolyte layer in an amount of 5 mass% or less from the viewpoint of preventing excessive aggregation of the solid electrolyte and enabling the formation of a solid electrolyte layer having a uniformly dispersed solid electrolyte.
[0065] The thickness of the solid electrolyte layer is not particularly limited, and is usually 0.1 μm or more and 1 mm or less. The method for forming the solid electrolyte layer includes a method of applying a paste for forming a solid electrolyte layer containing a solid electrolyte onto a support and drying it, and a method of pressurizing a powder of a solid electrolyte material containing a solid electrolyte. The support may be the same as those exemplified for the positive electrode layer. When pressurizing the powder of the solid electrolyte material, a press pressure of about 1 MPa or more and 2000 MPa or less is usually applied. The method of applying pressure is not particularly limited, but may be any of the pressure applying methods exemplified in the formation of the positive electrode layer.
[0066] The battery may optionally include an exterior body that houses a laminate having a positive electrode collector, a positive electrode layer, an electrolyte layer, a negative electrode layer, and a negative electrode collector in this order, and a restraining member. The material of the exterior body is not particularly limited as long as it is stable to the electrolyte, and examples of the material include polypropylene, polyethylene, and resins such as acrylic resin. The restraining member may be any known member usable as a battery restraining member as long as it can apply a restraining pressure in the stacking direction to the laminate. For example, a restraining member having plate-shaped parts that sandwich both surfaces of the laminate, a rod-shaped part that connects the two plate-shaped parts, and an adjustment part that is connected to the rod-shaped part and adjusts the restraining pressure by a screw structure or the like can be used. The adjustment part can apply a desired restraining pressure to the laminate. The restraining pressure is not particularly limited, but may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. By increasing the restraining pressure, there is an advantage that it is easier to improve the contact between the layers. On the other hand, the restraining pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less. If the restraining pressure is too high, the restraining member is required to have high rigidity, and the restraining member may become large. The battery may have only one of the above laminates, or may be formed by stacking a plurality of the laminates. EXAMPLES
[0067] [How to calculate binder hardness (elastic modulus)] The binder dispersed in water was thinly spread using a coating machine and dried at room temperature to produce a binder sheet 200 to 300 μm thick. The binder sheet was cut into a rectangular shape of 10 mm x 50 mm, and a tensile test was performed using an autograph. The conditions for the tensile test were: sheet sample width: 10 mm, chuck distance: 10 mm, and tensile speed: 50 mm / min. Figure 1 is a graph showing an example of the relationship between strain and test force. The elastic modulus (MPa) was calculated from the slope of the elastic region shown in Figure 1. The calculated results of the elastic modulus of the binder used in the negative electrode are shown in Table 1.
[0068] Comparative Example 1 [Preparation of positive electrode] LiNi as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 O2, acetylene black (AB) as a conductive material, and PVdF as a binder were weighed out so that the composition ratio of the positive electrode active material: conductive material: binder = 92.0: 5.0: 3.0 (solid weight ratio) was obtained by mixing them to prepare a positive electrode mixture. The prepared positive electrode mixture was applied to an aluminum foil as a positive electrode current collector, and dried at 100 ° C to form a positive electrode layer on the positive electrode current collector. After that, it was pressed to a predetermined thickness with a roll press to obtain a positive electrode.
[0069] [Preparation of negative electrode] Spheroidized graphite (aspect ratio 1.2) as the negative electrode active material, carboxymethyl cellulose (CMC) as the thickener, and SBR (hardness 115 MPa) as the binder were weighed out so that the composition ratio of the negative electrode active material: thickener: binder = 98.3 / 1.0 / 0.7 (solid weight ratio) was obtained by mixing them to prepare a negative electrode mixture. The prepared negative electrode mixture was applied to a Cu foil as a negative electrode current collector, and dried at 80 ° C. to form a negative electrode layer on the negative electrode current collector. After that, it was pressed to a predetermined thickness with a roll press with a linear pressure of 4 kN / m to obtain a negative electrode. The aspect ratio of the negative electrode active material was calculated from the ratio of the major axis to the minor axis of the negative electrode active material (major axis / minor axis).
[0070] [Preparation of evaluation cells] A PP / PE / PP (thickness: 20 μm) separator was prepared, and the positive electrode prepared above was laminated on one side of the separator so that the positive electrode layer was in contact with the separator, and the negative electrode prepared above was laminated on the other side so that the negative electrode layer was in contact with the separator, thereby obtaining a laminate. An electrolyte solution containing 1M LiPF6 as the electrolyte and a mixed solvent of EC / DMC / EMC = 3:4:3 vol% as the solvent was prepared, and the electrolyte solution was poured into the laminate placed in the case to impregnate the laminate with the electrolyte solution to produce an evaluation cell.
[0071] Comparative Example 2 In the above [Preparation of Negative Electrode], the prepared negative electrode mixture was applied onto a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes, and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. An evaluation cell was prepared in the same manner as in Comparative Example 1, except that the negative electrode mixture was applied onto a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes, and then dried at 80°C to form a negative electrode layer on the negative electrode current collector.
[0072] Comparative Example 3 An evaluation cell was produced in the same manner as in Comparative Example 1, except that in the above [Production of the negative electrode], an acrylic acid ester (hardness: 1886 MPa) was used as the binder.
[0073] Comparative Example 4 An evaluation cell was prepared in the same manner as in Comparative Example 1, except that in the above [Preparation of Negative Electrode], an acrylic acid ester (hardness: 1886 MPa) was used as a binder, the prepared negative electrode mixture was applied onto a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes, and then dried at 80°C to form a negative electrode layer on the negative electrode current collector.
[0074] Comparative Example 5 An evaluation cell was produced in the same manner as in Comparative Example 1, except that in the above [Production of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material.
[0075] Comparative Example 6 An evaluation cell was produced in the same manner as in Comparative Example 1, except that in the above [Production of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material and acrylic ester (hardness 1886 MPa) was used as the binder.
[0076] Comparative Example 7 An evaluation cell was prepared in the same manner as in Comparative Example 1, except that in the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, the prepared negative electrode mixture was coated on a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector.
[0077] Comparative Example 8 In the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, SBR (hardness 244 MPa) was used as the binder, the prepared negative electrode mixture was coated on a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. An evaluation cell was prepared in the same manner as in Comparative Example 1, except for this.
[0078] Comparative Example 9 In the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, a mixture (hardness 811 MPa) containing SBR (hardness 115 MPa) and acrylic acid ester (hardness 1886 MPa) in a weight ratio of SBR:acrylic acid ester = 2:1 was used as the binder, the prepared negative electrode mixture was coated on Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. Except for this, a cell for evaluation was prepared in the same manner as in Comparative Example 1.
[0079] Example 1 In the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, a mixture (hardness 1027 MPa) containing SBR (hardness 115 MPa) and acrylic acid ester (hardness 1886 MPa) in a weight ratio of SBR:acrylic acid ester = 1:1 was used as the binder, the prepared negative electrode mixture was coated on Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. Except for this, a cell for evaluation was prepared in the same manner as in Comparative Example 1.
[0080] Example 2 In the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, a mixture (hardness 1288 MPa) containing SBR (hardness 115 MPa) and acrylic acid ester (hardness 1886 MPa) in a weight ratio of SBR:acrylic acid ester = 1:2 was used as the binder, the prepared negative electrode mixture was coated on Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. Except for this, a cell for evaluation was prepared in the same manner as in Comparative Example 1.
[0081] Example 3 In the above [Preparation of Negative Electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, acrylic acid ester (hardness 1886 MPa) was used as the binder, the prepared negative electrode mixture was coated on a Cu foil as a negative electrode current collector, and the mixture was held under a magnetic field of 0.3 T for 3 minutes and then dried at 80°C to form a negative electrode layer on the negative electrode current collector. Except for this, a cell for evaluation was prepared in the same manner as in Comparative Example 1.
[0082] [Orientation degree I(110) / I(004) measurement] XRD of each of the negative electrodes produced in Comparative Examples 1 to 9 and Examples 1 to 3 was measured under the following conditions. Conditions: Tube Cu, Tube voltage 45kV, Tube current 200mA, Measurement angle 5~90deg, Step 0.02deg, Speed 10deg / min The degree of orientation I(110) / I(004) was calculated by dividing the 110 diffraction intensity I(110) of the obtained XRD data by the 004 diffraction intensity I(004). The results are shown in Table 1. The higher the degree of orientation, the more vertically the graphite stands.
[0083] [Battery resistance measurement] Each cell prepared in Comparative Examples 1 to 9 and Examples 1 to 3 was initially charged. Then, aging was performed at 60° C. Using this cell, charging was performed for 10 seconds at three arbitrary current value differences at SOC 50% in a −10° C. environment, and the slope of the relationship between the voltage difference ΔV before and after current application and the current value was calculated as the resistance value. FIG. 2 is a diagram showing an example of the relationship between the current and the voltage difference ΔV. In the above [Preparation of the negative electrode], flake graphite (aspect ratio 2.0) was used as the negative electrode active material, SBR (hardness 115 MPa) was used as the soft binder, and a magnetic field was applied to prepare a negative electrode. The resistance of the cell according to Comparative Example 7 was set as the reference (1.0), and the resistance of the cells according to each Example and Comparative Example was relativized and calculated as a resistance ratio. A resistance ratio of ±0.01 is considered to be equivalent performance. The results are shown in Table 1.
[0084] [Table 1]
[0085] [Evaluation Results] As shown in Examples 1 to 3 in Table 1, it was demonstrated that a cell using a negative electrode prepared by using flake graphite (aspect ratio 2.0) as the negative electrode active material, using a hard binder, and applying a magnetic field can reduce resistance. From the results of resistance reduction in Examples 1 to 3, it is predicted that if the orientation degree of the negative electrode active material is greater than 0.23, the cell resistance can be reduced, and if the orientation degree of the negative electrode active material is 0.25 or more, it is predicted that the cell resistance can be further reduced. As shown in Comparative Examples 1 to 4, when spherical graphite (aspect ratio 1.2) was used as the negative electrode active material, the degree of orientation of the negative electrode active material was low even when a magnetic field was applied, and the cell resistance increased. As shown in Comparative Example 6, when flake graphite (aspect ratio 2.0) is used as the negative electrode active material, a hard binder is used, and no magnetic field is applied, the degree of orientation of the negative electrode active material is low and the cell resistance increases. As shown in Comparative Examples 5 and 7, even when flake graphite (aspect ratio 2.0) is used as the negative electrode active material, the cell resistance increases when a soft binder is used and no magnetic field is applied. As shown in Comparative Examples 7 to 9 and Example 1, when the elastic modulus of the binder was in the range of 115 to 811, the cell resistance did not change even if the degree of orientation of the negative electrode active material increased, but it was confirmed from Example 1 and Comparative Example 9 that when the elastic modulus of the binder exceeded 811, the degree of orientation of the negative electrode active material increased, thereby reducing the cell resistance. This is believed to be because the use of a hard binder with a high elastic modulus maintains the orientation of the negative electrode active material even when a pressing pressure is applied to the negative electrode.
Claims
1. A negative electrode for a lithium ion secondary battery, The negative electrode includes a negative electrode current collector and a negative electrode layer, The negative electrode layer includes a negative electrode active material and a binder, The elastic modulus of the binder is greater than 811 MPa; When the X-ray diffraction intensity of the (110) plane of the negative electrode active material is I(110) and the X-ray diffraction intensity of the (004) plane is I(004), the degree of orientation I(110) / I(004) of the negative electrode active material obtained by dividing I(110) by I(004) is greater than 0.23; The negative electrode is characterized in that the negative electrode active material is flake graphite.
2. 10. The anode of claim 1, wherein the anode active material has an aspect ratio greater than 1.
2.
3. The negative electrode according to claim 1 or 2, wherein the binder has an elastic modulus of 3000 MPa or less.
4. The negative electrode according to claim 1 or 2, wherein the binder has an elastic modulus of 1886 MPa or less.
5. The negative electrode according to any one of claims 1 to 4, wherein the binder has an elastic modulus of 1027 MPa or more.
6. The negative electrode according to any one of claims 1 to 5, wherein the degree of orientation I(110) / I(004) is 0.25 or more.
Citation Information
Patent Citations
Manufacture of negative electrode for battery
JP1998321219A
Graphite powder and nonaqueous electrolyte secondary battery
JP2006083030A
Secondary battery
JP2013004307A
Secondary battery
JP2013089574A
Process for production of negative electrode for non-aqueous electrolyte secondary battery, negative electrode, and non-aqueous electrolyte secondary battery utilizing the negative electrode
WO2010146832A1